Fragmentation in disaster risk management systems: A barrier for integrated planning. (December 2015) - Rivera, Claudia; Tehler, Henrik; Wamsler, Christine
Abstract: The need to integrate climate change adaptation (CCA) considerations into disaster risk management (DRM) systems is widely recognised. However, successful integration, and thus the implementation of integrated planning measures, is difficult in practice. To understand and reduce the problems encountered, it is important to investigate systemic challenges. These challenges are rooted in the interaction between various stakeholders that affect DRM and the integration of CCA, directly or indirectly. This study explores the degree of integration in on-the-ground measures by studying systemic challenges, using the Nicaraguan DRM system as a case study. A theoretical framework for investigating systemic challenges in DRM systems was developed. It was then used in a retrospective analysis of the different functions of the systems in order to identify fragmentation in knowledge, information and coordination flows at local and national levels of governance. The results revealed several fragmented processes and functions in the Nicaraguan DRM system. These lead to difficulties in consolidating relevant information produced by multiple governmental authorities at different levels, and transferring this information to the local level. Fragmentation also leads, in turn, to little integration of CCA aspects into DRM in both local planning and practice.